ANALISIS KINERJA KEUANGAN PADA PT. BANK PEMBIAYAAN RAKYAT SYARIAH (BPRS) MUAMALAT HARKAT SUKARAJA - Suprotul Azwa; Sulisti Afriani (UNIVED Press, 2016)
Purpose of this study to determine the financial performance PT. Bank Pembiayaan Rakyat Syariah (BPRS) Muamalat Harkat Sukaraja. While the analysis using quantitative methods using financial ratios. The results showed that the financial performance PT. Bank Pembiayaan Rakyat Syariah (BPRS) Muamalat Harkat Sukaraja terms of liquidity (LDR) in 2013 with a ratio of 143.82% unwell and in 2014 with a ratio of 99.73% increased to be healthy. In terms of solvency (CAR) in 2013 with a ratio of 14.49% and 2014 with a ratio of 12.72% healthy. In terms of liquidity both ROA and BOPO healthy financial performance. Ratio ROA in 2013 with a ratio of 4.34% and in 2014 with a ratio of 2.58%. Ratio BOPO in 2013 with a ratio of 51.43% and in 2014 with a ratio of 58.29%, because it can utilize existing assets to obtain maximum profit and cost efficiency well. Key Words: Performance, Financial